1990
DOI: 10.2307/3586901
|View full text |Cite
|
Sign up to set email alerts
|

Reading-Writing Relationships in First and Second Language

Abstract: The study reported in this article examined the first language and second language reading and writing abilities of adult ESL learners to determine the relationships across languages (L1 and L2) and across modalities (reading and writing) in the acquisition of L2 literacy skills. Specifically, we investigated relationships (a) between literacy skills in a first language and literacy development in a second language (i.e., between reading in L1 and L2, and between writing in L1 and L2), and (b) between reading … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
95
0
5

Year Published

1995
1995
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(112 citation statements)
references
References 9 publications
(7 reference statements)
9
95
0
5
Order By: Relevance
“…This finding not only supports Cummins's (1981) Interdependence Hypothesis, but corroborates the results of previous research supporting the transfer phenomenon (Carson et al, 1990;Groebel, 1980;Reyes, 1987;Wagner et al, 1989; among many others). Evidently, language skills do transfer, allowing language students, particularly upper level students who have reached the necessary language threshold, to capitalize upon their LI skills in order to make sense of the L2.…”
Section: Consistencies In the Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…This finding not only supports Cummins's (1981) Interdependence Hypothesis, but corroborates the results of previous research supporting the transfer phenomenon (Carson et al, 1990;Groebel, 1980;Reyes, 1987;Wagner et al, 1989; among many others). Evidently, language skills do transfer, allowing language students, particularly upper level students who have reached the necessary language threshold, to capitalize upon their LI skills in order to make sense of the L2.…”
Section: Consistencies In the Resultssupporting
confidence: 81%
“…The positive correlations resulting from reading ability transfer studies (e.g., Carson, Carrell, Silberstein, Kroll, & Kuehn, 1990;Goldman, Reyes, & Varnhagen, 1984;Groebel, 1980;Reyes, 1987;Wagner, Spratt, & Ezzaki, 1989) uphold the idea that though the relationship between LI and L2 reading may vary according to L2 proficiency level, or other factors such as text genre, reading proficiency can transfer between languages.…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…For instance, Carson, Carrell, Silberstein, Kroll, and Kuehn (1990) examined the correlation between first and second language writing performance of 57 Japanese students and 48 Chinese students Japanese. The results of their study revealed a weak but positive correlation between writing skills of Japanese students (r =.23) but they did not find a positive relationship for Chinese students' composition skills (r = -.19).…”
Section: Related Studiesmentioning
confidence: 99%